PELATIHAN BACK EXERCISE PADA IBU HAMIL TRIMESTER III - Yustiari; Yulita, Hendra; Wahida; Aswita (Poltekkes Kemenkes Kendari, 2024)
As older people get older, there is a decline in the elderly's memory. Many elderly people forget something. If left unchecked, memory loss will ultimately impact the quality of life of the elderly. Memory as part of the cognitive function of the elderly needs to be improved. The aim of this community service is to improve the ability of the elderly to independently practice brain gymnastics in an effort to improve cognitive function in the elderly, as a preventive and promotive activity for the health of the elderly. Brain exercise therapy was attended by 12 elderly people in the RT 06 RW 01 area, Tanjungrejo sub-district, Sukun District, Malang City, which was carried out at the house of one of the residents. The activity is carried out in 2 sessions, namely a training session and a therapy session, consisting of 9 hand movements that train the balance of the right and left brain. The results of the activity showed that there were 5 elderly people who could do brain exercises independently and 7 other elderly people could do it with help. This activity went well, the elderly were enthusiastic about this activity which was seen through sentences and body gestures as well as excitement in doing brain exercises. With this activity, the Service concluded that this training had a success of 42% to be able to practice brain gymnastics therapy in improving the cognitive health of the elderly.